2018 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2018
DOI: 10.1109/icassp.2018.8462215
|View full text |Cite
|
Sign up to set email alerts
|

Deep Stock Representation Learning: From Candlestick Charts to Investment Decisions

Abstract: We propose a novel investment decision strategy (IDS) based on deep learning. The performance of many IDSs is affected by stock similarity. Most existing stock similarity measurements have the problems: (a) The linear nature of many measurements cannot capture nonlinear stock dynamics; (b) The estimation of many similarity metrics (e.g. covariance) needs very long period historic data (e.g. 3K days) which cannot represent current market effectively; (c) They cannot capture translation-invariance. To solve thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 18 publications
0
32
0
Order By: Relevance
“…Reading candlestick charts allows traders to understand impacts of trends called visual features rather than reading numerical raw data directly. Some recent investigations manifest that analyzing visual characteristics of candlestick charts to predict stock market is still a hot topic, for examples, Hu et al [8] summarize the historical financial data as images using candlestick charts and adopt the convolutional autoencoder for feature learning from the image data, Fengqian and Chao [25] apply K-line theory to characterize candlesticks as a generalization of price movements over a time period and then propose the deep reinforcement learning based system to reach adaptive control in the unknown environment, and Ananthi and Vijayakumar [26] proposed a system that generates signals on the candlesticks to predict market price movement by using regression and candlestick pattern detection. Furthermore, a novel variation of conventional candlesticks, RGBSticks, is introduced in [27] to predict the daily stock price of a company by using an autoencoder based on deep neural network.…”
Section: Analysis Of Candlestick Chartsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reading candlestick charts allows traders to understand impacts of trends called visual features rather than reading numerical raw data directly. Some recent investigations manifest that analyzing visual characteristics of candlestick charts to predict stock market is still a hot topic, for examples, Hu et al [8] summarize the historical financial data as images using candlestick charts and adopt the convolutional autoencoder for feature learning from the image data, Fengqian and Chao [25] apply K-line theory to characterize candlesticks as a generalization of price movements over a time period and then propose the deep reinforcement learning based system to reach adaptive control in the unknown environment, and Ananthi and Vijayakumar [26] proposed a system that generates signals on the candlesticks to predict market price movement by using regression and candlestick pattern detection. Furthermore, a novel variation of conventional candlesticks, RGBSticks, is introduced in [27] to predict the daily stock price of a company by using an autoencoder based on deep neural network.…”
Section: Analysis Of Candlestick Chartsmentioning
confidence: 99%
“…It is easy to recognize visual trends from candlestick charts and use the corresponding information collected to help predict price movements. Although the literature has shown that candlestick pattern analysis is a successful approach in financial forecasting [7][8][9][10], predicting the price movements by reading the visual trends from candlestick charts is still challenging. One can argue that nuances are lost in the candlestick charts while candlestick charts simplifies complex analysis behind the scene.…”
Section: Introductionmentioning
confidence: 99%
“…Huy et al (2017) developed a new prediction model based on both online financial news and past stock price data to predict stock movements in advance [8]. Hu et al (2017) proposed a novel investment decision strategy based on deep learning. Key idea is to endow an algorithmic strategy with the ability to make decisions with a similar kind of visual cues used by human traders.…”
Section: Related Workmentioning
confidence: 99%
“…Key idea is to endow an algorithmic strategy with the ability to make decisions with a similar kind of visual cues used by human traders. To this end we apply Convolutional Auto Encoder (CAE) to learn an asset representation based on visual inspection of the asset's trading history [18].…”
Section: Related Workmentioning
confidence: 99%
“…The Investors who invest in the stock market will analyze the condition of the company to get maximum profit (Hu et al, 2018;Lee, Cho, Kwon, & Sohn, 2019). The Investors will look for prospective companies by considering external and internal factors (Rao, Chandy, & Prabhu, 2008;Sujoko, 2017).…”
Section: Introductionmentioning
confidence: 99%